“The impacts of the brand value assigned by consumers on their brand attitude and purchase intention: The analysis of Hassu and Saudade Jewels brands” - Pereira, Inês Alexandra Veiga (2022)
The present research aims to analyze the relationship between brand equity, brand attitude and purchase intention in Hassu and Saudade Jewels brands. Therefore, following Yoo and Donthu's model, brand equity was divided into three dimensions: brand awareness + brand associations, perceived quality and brand loyalty, and these dimensions were used as antecedents of brand attitude. In addition, brand attitude was measured as an antecedent of purchase intention. The study contributed by applying these models to the context of the Flamingo S.A. company. It was decided to investigate two different brands: Hassu brand and Saudade Jewels brand, to recognize the differences between their publics. In this sense, a quantitative methodology was used, having obtained 181 valid answers through the application of a questionnaire. For data analysis Exploratory Factor Analysis was used, as well as the statistical tests necessary to validate the research hypotheses were performed. The results of this study suggest that brand equity applied to the brands under study is composed of 2 dimensions (Brand Awareness + Brand Associations and Perceived Quality + Brand Loyalty). Likewise, it was found that brand awareness + brand associations and perceived quality + brand loyalty have a positive impact on brand attitude which, in turn, has a positive impact on the intention to purchase, being these results valid for both brands.